Variety and phosphate fertilizer dose effect on nutrient composition, in vitro digestibility and feeding value of cowpea haulm. Issue 1 (December 2016) - Ansah, Terry; Algma, Henry; Dei, Herbert
Abstract Background Cowpea (Vigna unguiculata [L.]) is a legume cultivated throughout most tropical countries and is valued as food and feed for human and livestock respectively. The search for an improved cowpea variety has been on-going with the aim of improving traits such as grain yield, drought and pest resistance. But no information exist on the feeding value of these improved varieties. Phosphate (P) fertilizer application is recommended to augment grain yield in grain legumes but data on the effect of P fertilizer on haulm quality is limited. Results Two separate experiments were conducted to determine the effect of P fertilizer dose on the nutritive value of haulms from different cowpea varieties (V). In experiment 1, effect of three P doses (30, 60 and 90 kg P2 O5 /ha) on in vitro gas production (IVGP) characteristics, concentrations of digestible organic matter (DOM), crude protein (CP), acid detergent fiber (ADF) and neutral detergent fiber (NDF) of haulms from five cowpea varieties (Zaayura-SARC 4-75, Songotra-IT97K-499-35, Hewale-IT93K-192-4, IT99K 573-1-1 and Asomdwe-IT94K-410-2) were investigated using the 3 (P) x 5 (V) factorial treatment arrangements in a completely randomized design. In experiment 2, the effects of two P doses (30 and 90 kg P2 O5 /ha) and two varieties (Zaayura-SARC 4-75 and Hewale-IT93K-192-4) on the voluntary feed intake, live weight, haematology and carcass characteristics of Djallonke lambs were also assessed using a 2(P) x 2(V) factorial treatment arrangement. The V x P interaction significantly affected CP, NDF and ADF with CP concentration increasing with increase in P doses in Zaayura-SARC 4-75 and Asomdwe-IT94K-410-2. Whilst an increase (P <  0.05) in NDF was observed in Songotra-IT97K-499-35and Asomdwe-IT94K-410-2 as P doses increased, the other V only increased from P dose 30 to 60 kg/ha and declined at P dose 90 kg/ha. The ADF decreased (P  < 0.05) with increase in P dose for all V with the exception of Songotra-IT97K-499-35. There was a significant V effect on DOM with the highest reported in Zaayura-SARC 4-75 (43.44 %). Daily DM intake, carcass length and blood urea nitrogen of the lambs were significantly affected by the V x P interaction. There was a significant V effect on globulin and P effect on live weight at slaughter, dressed weight, chuck, leg, loin, rib and flank and liver and lungs. Conclusion It can be concluded that nutrient concentrations of cowpea haulms were positively influenced by different P dose and varieties with favorable effects on growth, haematology and carcass composition of lambs. Varieties Zaayura-SARC 4-75 and Hewale-IT93K-192-4 at P dose at 90 kg/ha are recommended to enhance growth performance and carcass yield of Djallonke lambs.